Menilik Pendidikan Karakter Di Berbagai Negara (Studi Multi Situs Di Indonesia, Singapura Dan Jepang) - Arif Syamsurrijal (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, Character education in the grand design of character education, is theprocess of civilizing and empowering noble values in the educational unit environment(school, family environment, and community environment). These noble values comefrom theories of education, educational psychology, socio-cultural values, religiousteachings, Pancasila, the 1945 Constitution, and Law Number 20 of 2003 concerningthe National Education System and the best experiences and real practices ineveryday life. Then, what is the practice of character education in Indonesia today? Inthis short article, the author conducted a literature study related to the concept andimplementation of character education in schools in three countries, namelyIndonesia, Singapore and Japan, with the consideration that Education in Singaporeand Japan became one of the best in the world when this. Keywords: education, character education, Indonesia, Singapore, Japan